THE PERCEPTION OF PARENTS TOWARD INCLUSIVE EDUCATION: CASE STUDY IN INDONESIA - Rasmitadila, .; Widyasari, .; Prasetyo, Teguh; Rachmadtullah, Reza; Nuraeni, Yeni (PEOPLE: International Journal of Social Sciences, 2019)
This study aims to explore the perceptions of parents of regular students (PRS) and parents of special needs students (PSNS) alike on inclusive education at the elementary school level in Indonesia. This study was a case study-type qualitative research. The data collection consisted of a questionnaire and in-depth interviews. The participants in this study were 89 PRSs and 42 PSNS in West Java Indonesia. The findings of the study displayed that the perception of PRSs and PSNSs on inclusive education can be categorized into four aspects, namely social, emotional, academic, and non-academic. The perception of social elements can develop communication, social interaction, play, and cooperation between students. The emotional aspect develops a sense of respect, empathy, love, and caring for each other, respecting differences, while at the same time generating SNS insecurity when in an inclusive classroom. As far as academic aspects are concerned to provide opportunities for SNSs and RSs to learn together. Besides, there is a tendency that the teacher cannot always allocate time in order to give more attention to the SNSs than to the RSs. Perception of non-academic aspects that inclusive education is a service that provides every child with the right to access education.